2009
DOI: 10.1371/journal.pgen.1000434
|View full text |Cite
|
Sign up to set email alerts
|

Alliance of Proteomics and Genomics to Unravel the Specificities of Sahara Bacterium Deinococcus deserti

Abstract: To better understand adaptation to harsh conditions encountered in hot arid deserts, we report the first complete genome sequence and proteome analysis of a bacterium, Deinococcus deserti VCD115, isolated from Sahara surface sand. Its genome consists of a 2.8-Mb chromosome and three large plasmids of 324 kb, 314 kb, and 396 kb. Accurate primary genome annotation of its 3,455 genes was guided by extensive proteome shotgun analysis. From the large corpus of MS/MS spectra recorded, 1,348 proteins were uncovered a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
206
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 154 publications
(215 citation statements)
references
References 53 publications
5
206
0
Order By: Relevance
“…As recAP1 and recAP3 code for identical proteins, these results indicate that recAP3 expression is weak compared with that of recAP1, at least under the experimental conditions used. This is in agreement with our previously reported RT-PCR data that indicated that recAP3 transcription levels are lower than that of recAP1 and recAC (de Groot et al, 2009). The promoter activities of recAP1 and recAP3 may be different: the first 72 bp upstream of their start codons is nearly identical (only one difference), but the sequences further upstream are different.…”
Section: Each Single Reca Mutant Is As Uv and Gamma Radiation-resistasupporting
confidence: 93%
See 3 more Smart Citations
“…As recAP1 and recAP3 code for identical proteins, these results indicate that recAP3 expression is weak compared with that of recAP1, at least under the experimental conditions used. This is in agreement with our previously reported RT-PCR data that indicated that recAP3 transcription levels are lower than that of recAP1 and recAC (de Groot et al, 2009). The promoter activities of recAP1 and recAP3 may be different: the first 72 bp upstream of their start codons is nearly identical (only one difference), but the sequences further upstream are different.…”
Section: Each Single Reca Mutant Is As Uv and Gamma Radiation-resistasupporting
confidence: 93%
“…It has also three different recA genes (Deide_19450, Deide_1p01260 and Deide_3p00210, present on the chromosome, plasmid P1 and plasmid P3 respectively). Except for Deide_1p00180, transcription of all these genes was induced after exposure of D. deserti to UV, suggesting a role in the DNA damage response (de Groot et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…NanoLC‐MS/MS experiments were performed using a LTQ‐Orbitrap XL hybrid mass spectrometer (ThermoFisher) coupled to an UltiMate 3000 LC system (Dionex‐LC Packings). Conditions used were those previously described (de Groot et al ., 2009). …”
Section: Methodsmentioning
confidence: 99%